Growth hormone secretagogue receptor in dopamine neurons controls appetitive and consummatory behaviors towards high-fat diet in ad-libitum fed mice. (September 2020) - Cornejo, María Paula; Barrile, Franco; Cassano, Daniela; Aguggia, Julieta Paola; García Romero, Guadalupe; Reynaldo, Mirta; Andreoli, María Florencia; De Francesco, Pablo Nicolás; Perello, Mario
Highlights: GHSR in DA neurons is sufficient to control reward-related behaviors towards HF diet, in the absence of caloric needs. GHSR exclusively in DA neurons is sufficient to orchestrate binge-like HF intake. GHSR in DA neurons is sufficient to mediate increased anticipatory activity to a scheduled HF diet exposure. GHSR in DA neurons is insufficient to mediate ghrelin's effect on food intake, food seeking and locomotor activity. Abstract: Growth hormone secretagogue receptor (GHSR), the receptor for ghrelin, is expressed in key brain nuclei that regulate food intake. The dopamine (DA) pathways have long been recognized to play key roles mediating GHSR effects on feeding behaviors. Here, we aimed to determine the role of GHSR in DA neurons controlling appetitive and consummatory behaviors towards high fat (HF) diet. For this purpose, we crossed reactivable GHSR-deficient mice with DA transporter (DAT)-Cre mice, which express Cre recombinase under the DAT promoter that is active exclusively in DA neurons, to generate mice with GHSR expression limited to DA neurons (DAT-GHSR mice). We found that DAT-GHSR mice show an increase of c-Fos levels in brain areas containing DA neurons after ghrelin treatment, in a similar fashion as seen in wild-type mice; however, they did not increase food intake or locomotor activity in response to systemically- or centrally-administered ghrelin. In addition, we found that satiated DAT-GHSR mice displayed both anticipatory activity to scheduled HF diet exposure and HF intake in a binge-like eating protocol similar to those in wild-type mice, whereas GHSR-deficient mice displayed impaired responses. We conclude that GHSR expression in DA neurons is sufficient to both mediate increased anticipatory activity to a scheduled HF diet exposure and fully orchestrate binge-like HF intake, but it is insufficient to restore the acute orexigenic or locomotor effects of ghrelin treatment. Thus, GHSR in DA neurons affects appetitive and consummatory behaviors towards HF diet that take place in the absence of caloric needs.